The Influence of Green Human Resource Management and Green Organizational Culture on Environmental Performance as Mediated Green Innovation Variables - Sayed Syahridhan (Dinasti Publisher, 2024)
The purpose of this literature study is expected to build a hypothesis regarding the influence between variables that can later be used for further research in the scope of human resource management. The literature review research article on the influence of green human resource management and green organizational culture on environmental performance mediated by green innovation variables is a scientific literature article in the scope of human resource management science. The approach used in this literature review research is descriptive qualitative. The data collection technique is to use literature studies or conduct a review of relevant previous articles. The data used in this descriptive qualitative approach comes from previous research that is relevant to this research and is sourced from academic online media such as the Thomson Reuters Journal, Springer, Taylor & Francis, Scopus Emerald, Elsevier, Sage, Web of Science, Sinta Journal, DOAJ, EBSCO, Google Scholar and digital reference books. In previous studies, 1 relevant previous article was used to review each independent variable. The results of this literature review article are: 1) Green HR Management influences Green Innovation; 2) Green Organizational Culture influences Green Innovation; 3) Green HR Management influences Environmental Performance; 4) Green Organizational Culture influences Environmental Performance; 5) Green Innovation influences Environmental Performance; 6) Green Human Resource Management influences Environmental Performance mediated by Green Innovation; and 7) Green Organizational Culture influences Environmental Performance mediated by Green Innovation.